2016
DOI: 10.1016/j.jclepro.2016.05.189
|View full text |Cite
|
Sign up to set email alerts
|

A technical evaluation, performance analysis and risk assessment of multiple novel oxy-turbine power cycles with complete CO2 capture

Abstract: In recent years there has been growing concern about greenhouse gas emissions (particularly CO2 emissions) and global warming. Oxyfuel combustion is one of the key technologies for tackling CO2 emissions in the power industry and reducing their contribution to global warming. The technology involves burning fuel with high-purity oxygen to generate mainly CO2 and steam, enabling easy CO2 separation from the flue gases by steam condensation. In fact, 100% CO2 capture and near-zero NOx emissions can be achieved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Some of the main studies on oxy fuel combustion are listed in Table 5. Climent et al [112] 2016 Analyzed different oxy turbine power cycles with complete carbon capture for better performance.…”
Section: Oxy-combustion Carbon Capturementioning
confidence: 99%
“…Some of the main studies on oxy fuel combustion are listed in Table 5. Climent et al [112] 2016 Analyzed different oxy turbine power cycles with complete carbon capture for better performance.…”
Section: Oxy-combustion Carbon Capturementioning
confidence: 99%
“…In particular, it can be used to analyze and break down various problems more holistically. PESTLE analysis has recently been applied to certain industrial sectors, such as the conventional, fossil-fuel [6,7] as well as renewable [8][9][10] energy industries. By using PESTLE analysis, new strategic policies can be developed to replace and renew policies that are no longer effective or efficient.…”
Section: Research Approachmentioning
confidence: 99%
“…The recycled stream will be predominantly CO 2 and/or H 2 O, i.e., for CO 2 ‐based and water‐based oxy‐combustion cycles, respectively . As will be discussed in detail later, the former includes semi‐closed oxy‐combustion combined cycles and high‐pressure CO 2 supercritical cycles, whereas water‐based cycles comprise the CES and Graz cycles . Other alternative configurations integrate oxygen production in the cycle by using high‐temperature membranes (i.e., ZEITMOP and AZEP cycles).…”
Section: Oxy‐fired Gas Turbinesmentioning
confidence: 99%
“…A 20 MW th pilot test facility has assessed the operation of the high‐pressure, high‐temperature gas generator, at temperatures >1600°C and pressures in excess of 100 bar, and it is reported that the CAPEX can be half that of a combined cycle turbine . It has more recently been reported that the CES cycle produces favorable results in terms of technology and environment; however, it is still under development to demonstrate the technology …”
Section: Oxy‐fired Gas Turbinesmentioning
confidence: 99%